Existence of Nonoscillatory Solutions of Higher Order Nonlinear Neutral Differential Equations (European Journal of Pure and Applied Mathematics, 2023)
In this paper, an $n$-th order neutral nonlinear differential equation is studied. By using the Banach contraction principle, some sufficient conditions are established for the existence of nonoscillatory solutions of nonlinear $n$-th order neutral differential equation. An example is included to illustrate the results obtained.
Keywords: Fixed point, Higher-order, Neutral differential equation, Nonoscillatory solution